Caring Schools and Educators a Solution to Disparities in Academic Performance: Learners of Colors Speak. (April 2019) - Nganga, Lydiah; Kambutu, John; Han, Keonghee Tao
Disparities in academic performance based on race in the United States are a persistent problem. As a result, a plethora of remedies such as using student-centered instructional strategies, de-tracking, ensuring low teacher–student ratios, and promoting high teacher expectations for all learners have been tried with limited success. Thus, this phenomenological qualitative study explored other possible solutions from the experiences and perspectives of students. Participants were 33 high school students of color. 1 Data showed that the participating learners considered the use of culturally inclusive 2 teaching practices and learning resources, implemented in caring schools by caring educators a viable solution to issues of poor academic performance among learners of color.